Pass the Bucks: Credit, Blame, and the Global Competition for Investment. Issue 3 (6th December 2013) - Jensen, Nathan M.; Malesky, Edmund; Medina, Mariana; Ozdemir, Ugur
Abstract : Both countries and subnational governments commonly engage in competition for mobile capital, offering generous incentives to attract investment. Existing economics research has suggested that these tax incentives have a limited ability to affect investment patterns and are often excessively costly when measured against the amount of investment and jobs created. In this paper, we argue instead that the "competition" for capital can be politically beneficial to incumbent politicians. Building off work on electoral pandering, we argue that incentives allow politicians to take credit for firms' investment decisions. We test the empirical implications of this theory using a nationwide Internet survey, which employs a randomized experiment to test how voters evaluate the performance of incumbent US governors. Our findings illustrate a critical political benefit of offering such incentives. Politicians can use these incentives to take credit for investment flowing into their districts and to minimize the political fallout when investors choose to locate elsewhere.